MANAJEMEN KONFLIK DALAM LEMBAGA PENDIDIKAN - Efferi, Adri (Pascasarjana IAIN Kudus, 2013)
Conflict in the world of education is seen as one of the weak points in the management of educational institutions. This perspectiveemerged due to the institution managers view conflict as somethingnegative and counterproductive. The conflict in the organization isdirectly proportional to the age of the organization, including one ofwhich is the educational institution. Beginning of the conflict can beborn of issues that could be considered trivial or simple. However,it is not uncommon to be a determinant of lifespan or future survival of an organization for the duration of time much longer. Therefore, need proper management to resolve the conflict.